2011
DOI: 10.1007/s13280-011-0203-z
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Dissolved Organic Carbon Dynamics at the Swedish Integrated Monitoring Sites with the Integrated Catchments Model for Carbon, INCA-C

Abstract: Surface water concentrations of dissolved organic carbon ([DOC]) are changing throughout the northern hemisphere due to changes in climate, land use and acid deposition. However, the relative importance of these drivers is unclear. Here, we use the Integrated Catchments model for Carbon (INCA-C) to simulate longterm (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Model simulations of streamwater chemistry based on lumped data from hydraulically different compartments of the catchment may thus be flawed. Further discussion of this issue is presented in this volume by Futter et al (2011), Köhler et al (2011), andWinterdahl et al (2011).…”
Section: Differences Between Recharge and Discharge Areasmentioning
confidence: 99%
“…Model simulations of streamwater chemistry based on lumped data from hydraulically different compartments of the catchment may thus be flawed. Further discussion of this issue is presented in this volume by Futter et al (2011), Köhler et al (2011), andWinterdahl et al (2011).…”
Section: Differences Between Recharge and Discharge Areasmentioning
confidence: 99%
“…A recent long-term, cross-regional scale study by Laudon et al (2012) concluded that long-term average stream [DOC] is related to the prevailing mean annual temperature on a regional scale. When catchments across a 1000 km latitudinal gradient between Northern and Southern Sweden were compared, temperature and discharge both appeared as major controls, but differed in their importance for specific catchments (Winterdahl et al, 2011b;Futter et al, 2011). However, no consensus on how climatic factors are affecting stream chemical parameters in individual catchments has been reached for the northern boreal ecozone.…”
Section: Climate Control On Docmentioning
confidence: 99%
“…Here we present an extended version of the soil temperature model [33] used in the INCA suite of integrated catchment models [34]–. The objective of this study is to address the question of how future climate change could affect soil temperature response in a set of well-monitored forest sites aligned in a south-north gradient in Sweden.…”
Section: Introductionmentioning
confidence: 99%